Designing a computer-facilitated learning-tool for learning near-synonyms in Chinese - Ouyang, Shixiao. (2009)
Choosing an appropriate word from a cluster of near-synonyms is a significant challenge in second language acquisition. Second language learners (L2 learners) are found facing difficulties in distinguishing words that have similar meanings. The near-synonyms of physical action verbs (PA Verbs) for instance can be distinctive from each other in the way in which their actions are depicted linguistically. Gao [1] provided a demonstration of her decomposition method of the semantic properties of sub-classes of near-synonyms of Chinese PA Verbs, where differences among the near-synonyms are identified by investigation of meaning components, marked by different notions found in PA Verbs, such as Bodypart Contact, Instrument, Force, Motion Direction, Speed, Effect, Intention, and Patient Object etc. Based on her study, we propose an e-learning tool to facilitate advanced L2 learners in choosing the most appropriate PA Verb from a group of near-synonyms according to his/her intended context.